2009
DOI: 10.1002/jso.21293
|View full text |Cite
|
Sign up to set email alerts
|

Should we use laparoscopic adrenalectomy for metastases? Scandinavian multicenter study

Abstract: Laparoscopic adrenalectomy for metastases is feasible regardless of their sizes. However these procedures should be performed by highly skilled laparoscopic surgeon in a fully equipped operating room and with a coordinated operation team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 34 publications
2
49
0
6
Order By: Relevance
“…For example, a previous study claims that adrenalectomy has not proven beneficial in the treatment of patients with adrenal metastases following resection of colorectal hepatic metastases (26). However, other studies argued that laparoscopic adrenalectomy had its advantages compared to traditional open surgery, and improved the survival of patients with adrenal metastases (27). In the present study, laparoscopic adrenalectomy was found to be beneficial; however, the survival of patients with laparoscopic adrenalectomy did not appear to be different from that of patients with open surgery (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a previous study claims that adrenalectomy has not proven beneficial in the treatment of patients with adrenal metastases following resection of colorectal hepatic metastases (26). However, other studies argued that laparoscopic adrenalectomy had its advantages compared to traditional open surgery, and improved the survival of patients with adrenal metastases (27). In the present study, laparoscopic adrenalectomy was found to be beneficial; however, the survival of patients with laparoscopic adrenalectomy did not appear to be different from that of patients with open surgery (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…However, the introduction of laparoscopy has rendered surgery the primary treating modality of adrenal metastases. Laparoscopic approach has been proven to be as effective as open surgery [4,25], with the former associated with less blood loss (63±8 mL versus 2,207±1,067 mL, P00.05), a lower complication rate (0% versus 63%, P0 0.009), and a shorter length of stay [26]. Contraindications to laparoscopic surgery include pregnancy, large tumors (>8 cm), or suspicion of primary invasive adrenocortical carcinoma on imaging.…”
Section: Surgerymentioning
confidence: 99%
“…Surgical complication rate ranged between 4% and 29.4% [26,27,29,30]. Complications include deep venous thrombosis, pulmonary embolism, stroke, pneumonia, hematoma, myocardiac infarction, atelectasis, bowel perforation, lung infection, and wound infection [25,27,31]. Recurrence rate was reported to be between 0-21% [26,30], and the 5-year survival between 22.5% and 47% [4,26].…”
Section: Surgerymentioning
confidence: 99%
“…However, bilateral LA is effective for bilateral adrenal hyperplasia, neoplasmas or Cushing's syndrome (Fernández-Cruz et al 1996). The role of LA in patients with large adrenal lesions (> 6 cm), or potential malignancy remains controversial (Sturgeon and kebebew 2004;Cobb et al 2005;Tsuru et al 2005 ;Ramacciato et al 2008;Toniato et al 2007;Eto et al 2008;Marangos et al 2009). Pheochromocytoma is no longer considered a contraindication for LA, provided the appropriate drug treatment is carried out before surgery (alpha followed by beta-receptor or calcium channel blockers) (Toniato et al 2007;Humphrey et al 2008).…”
Section: Indicationsmentioning
confidence: 99%
“…Pheochromocytoma is no longer considered a contraindication for LA, provided the appropriate drug treatment is carried out before surgery (alpha followed by beta-receptor or calcium channel blockers) (Toniato et al 2007;Humphrey et al 2008). The effectiveness of LA for adrenocortical carcinoma and metastatic adrenal disease remains debatable (Gagner et al 1997;Fazeli-Matin et al 1999;Sturgeon and Kebebew 2004;Cobb et al 2005;Tsuru et al 2005;Eto et al 2008;Choh and Madura 2009;Marangos et al 2009;Turner et al 2009). When operating the adrenals for malignancy, the most important concern is whether the laparoscopic resection can achieve an equal oncological result in comparison with open surgery, the long-term survival and the risk of topical recurrence.…”
Section: Indicationsmentioning
confidence: 99%